HUBUNGAN ANTARA KOMUNIKASI DAN KUALITAS PERAWAT TERHADAP KEPUASAN KELUARGA PASIEN ICU - Shinta Dewi Kasih Bratha; Jogi Anggara; Hamdhani Hamdhani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Families of patients in the ICU often experience psychological stress, so their satisfaction becomes a key indicator of service quality. This study aims to analyze the relationship between communication and nurse quality with the satisfaction of ICU patients' families at X Hospital in Pekanbaru. Using a cross-sectional quantitative design, the sample involved 30 respondents. Data were collected through questionnaires and analyzed using the Chi-Square test. The univariate results showed that the majority of respondents rated communication as good (76.67%) and nurse quality as positive (83.33%). Bivariate tests showed a significant relationship between communication (p=0.000), quality (p=0.000), and family satisfaction. Overall satisfaction reached 90%. There is a link between nurses' interpersonal aspects and family satisfaction; the better the communication and nurse quality, the higher the satisfaction felt. Hospital management is advised to maintain these service standards and provide regular training on therapeutic communication, empathy management, and nurse quality to support the psychological stability of patients' families in critical care units.Keywords: Communication, Quality, Nurses, Satisfaction, Family. ICU